Aquifer vulnerability to pesticide leaching and its impact on groundwater - Anwar, Faisal; Saing, Lawrence (Jerad Publications, 2010)
In this paper, aquifer vulnerability to pesticide leaching was studied by computing Vulnerability Indices (VI) for 24 different pesticides in Ord River Irrigation Area (ORIA), Western Australia. VI methodology uses one-dimensional advective-dispersive transport equation for a non-conservative chemical that follows first order decay and linear adsorption in soils. At first, the pesticides were classified based on their leachabilty ratio (t1/2/koc). Next, grid lines were constructed on the map of the study area and 160 locations were marked to calculate VI for all pesticides. Calculated vulnerability indices were ranked by quartiles for very high, high, moderate, low and very low category for all the locations in the study area to find out the most vulnerable sites. Same classification was also made for all the pesticides in each location to rank the pesticides based on their individual VI. Based on the results obtained and the frequency of uses, it was revealed that atrazine has the highest leaching potential in the study area. The most vulnerable site for atrazine leaching was checked using the available groundwater quality data and found that the atrazine concentration exceeds the Australian and New Zealand guidelines (>0.5μg/L) in this site.